Two Separate Small and Large Ischemic Bowel Events Secondary to Sigmoid Adenocarcinoma: A Case Report - AlAyoubi, Alamir-Noureddine; Ghattas, Souad; Maalouf, Hani; Chahine, Georges; Kiriakos, Kiril; Fares, Mirna (The Surgery Journal, 2024)
Colonic obstruction is reported in 85% of emergency colorectal surgery for cancer. Colonic ischemia, however, is a rare entity and is found in 5% of these emergency cases. We herein present the case of a 72-year-old man presenting with signs and symptoms of obstruction and was found to have an obstructive sigmoid cancer. A first urgent laparotomy showed small bowel ischemia, for which small bowel resection and large bowel decompression were done without tumor resection. Postoperatively, the patient transiently improved, then deteriorated in few days, and a second urgent laparotomy showed a large bowel ischemia proximal to the mass. The treatment for patients with colon cancer with suspected colonic ischemia should be emergency laparotomy with long abdominal incision, carefully exploring the whole length of the small and large bowel. Despite large bowel decompression, a secondary colonic ischemic event should be suspected in case of deterioration.
Keywords: sigmoid adenocarcinoma; acute necrotizing colitis; obstructive colitis; ischemic colitis; small bowels